The effect of e- program based on Flipped learning on academic achievement for basic eighth grade students in Khartoum State and their attitudes towards it. - Hassan, Prof. Esam Edris Kamtor Al (IJRDO- Journal of Educational Research, 2020)
This study was carried out to identify the effect of e- program based on Flipped Learning (FL) on academic achievement for basic eighth grade Students and their attitudes towards it. The researcher used quasi-experimental according to an e-program based on FL to teach the science course in our life at Khartoum State. A sample is selected numerating 36 students were divided into two equal groups: an experimental, that studied by using an e- program based on FL and control group that was studied by the traditional method. By using the appropriate statistical methods, the data was analyzed .The study concluded many results, the most important are: There are statistically significant differences at (α = 0.05) between the mean scores of the experimental group that studied by using an e- program based on FL and the control group that was studied by the traditional method in post- test, in favor of the experimental group. There are positive attitude among basic eighth graders towards using the FL -based e-program. In light of the results, the study recommended conducting courses and workshops for the teachers and students in Sudanese basic education to train them on the concept and strategy of FL before its application, providing general education schools with technological tools, modern laboratory devices, and high speed internet, that to help teacher to prepare the needed materials according to the flipped classroom strategy.